2018
DOI: 10.3389/fpls.2018.00283
|View full text |Cite
|
Sign up to set email alerts
|

Candidate DNA Barcode Tags Combined With High Resolution Melting (Bar-HRM) Curve Analysis for Authentication of Senna alexandrina Mill. With Validation in Crude Drugs

Abstract: Senna alexandrina (Fabaceae) is a globally recognized medicinal plant for its laxative properties as well as the only source of sennosides, and is highly exported bulk herb from India. Its major procurement is exclusively from limited cultivation, which leads to risks of deliberate or unintended adulteration. The market raw materials are in powdered or finished product form, which lead to difficulties in authentication. Here, DNA barcode tags based on chloroplast genes (rbcL and matK) and intergenic spacers (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…In order to prevent such scenarios, taxonomic evaluation must be performed based on plant morphology for species identification. In fact, in the case of dried and ground raw materials of medical plants, morphological observations for species identification has proven difficult or even impossible [2528]. Bar-HRM can be used as an alternative aid for taxonomic evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to prevent such scenarios, taxonomic evaluation must be performed based on plant morphology for species identification. In fact, in the case of dried and ground raw materials of medical plants, morphological observations for species identification has proven difficult or even impossible [2528]. Bar-HRM can be used as an alternative aid for taxonomic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, their anthraquinones are significantly different in several Senna species [17], which are likely to influence their biological activities. In addition, the raw materials produced by these plants are usually processed and/or modified into various products, such as powder capsules and herbal infusions, which can further contribute to difficulty in the species differentiation [2528]. Accurate species identification during the manufacturing process and data generation to support the use of herbal plants as complementary and alternative medicine (CAM) options is necessary for the safety, quality, and efficacy of medicinal plant ingredients [2528].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, it also could differentiate different family species, which illustrate that the rbcL gene is not only highly distinguished within the Asteraceae family, but also highly distinguished within most of vegetables. So, rbcL would be one of the best choices for DNA barcoding to distinguish between vegetables [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mishra, Shukla, and Sundaresan (2018) evaluated several barcode regions, namely rbcL , matK , psbA‐trnH , ITS, ITS1, and ITS2, aiming at developing an HRM approach for Senna authentication. The authors concluded that ITS1 region gave the best results and proposed its use as a biomarker to discriminate six tested Senna species by HRM.…”
Section: Current Genome‐based Approachesmentioning
confidence: 99%